Evaluation of Piezotome-Corticision Assisted Orthodontics in Retracting Upper Canine: A Split Mouth Design (Randomized Clinical Trial) - Al Refaii, Samer; El Harouni, Nadia; Osman, Aly (European Scientific Journal, ESJ, 2021)
Objectives: The aim of this randomized clinical trial is to investigate the rate of canine retraction at different time points between piezotome-corticision assisted and conventional orthodontics. Methods: Fifteen patients were submitted for upper first premolars extraction after leveling and alignment was achieved to facilitate canine retraction. They were randomly divided into test side and control side. On the test side, the canine was retracted using piezotome-corticision assisted orthodontics, while at the control side, the canine was retracted using conventional technique. Both groups were immediately loaded with a horizontal force of 150g for canine retraction. The distance between the canine bracket hook and the first molar band hook were recorded using a digital caliper. The measurements were accomplished immediately after piezosurgery at 1,2,4,8 and 12 week. Results: There was a statistically significant difference in the average amount of canine retraction between test and control groups (P<0.05). The canine on the test side was closed 6 weeks earlier than the control side. Conclusion: Piezocision is minimal invasive which accelerate the rate of canine of retraction approximately 1.5 times faster than that of conventional method.